Meningkatkan Hasil Belajar Siswa Dalam Materi Gerak Tari Kreasi Daerah Pada Mata Pelajaran Seni Budaya Dan Prakarya Dengan Menggunakan Metode Demonsdtrasi Pada Siswa Kelas IV Di SDN Kadubelang 3 Kecamatan Mekarjaya Provinsi Banten - Rifki Arif Nugraha; Pelawati; Ratna Dewi; Ade Farid Hasyim (Desanta Publisher, 2023)
This research is classroom action research (PTK) whose implementation includes four stages, namely planning,action, observation and reflection which consists of two cycles where each cycle is carried out in two meetings.totaling 15 students, 9 women and 6 men, data collection instruments using observation sheets and tests, dataanalysis techniques used, qualitative descriptive analysis and quantitative descriptive analysis. The success ofthis research can be seen from the student learning outcomes which have increased in cycle 1 and cycle II.shows that it consists of increasing student learning outcomes in arts, culture and crafts (SBDP) subjects usingthe demonstration method of completion results in cycle I, namely from 15 students 13.3% cycle II 66.6% cycleIII 86.6%